Ялыке! - Перевозчикова Татьяна Григорьевна (Удмуртия, 1984)
Экземпляры: ф.11 (20181023) / Инвентарный номер: 12192 / Цена: 0.85 / Сис.шифр: 82.3(2) / Авт.знак: Я 53 / ГРНТИ: 17 / ББК: 82.3(2Рос=Удм).06